Bending strength and Biological properties of PLA-HA composites for femoral canine bone fixation plate - Saksorn Sadudeethanakul (2020)
© Published under licence by IOP Publishing Ltd. This research is based on the purposes to find suitable hot compression conditions of composites materials, also to optimize mechanical and biological properties of the plate specimen. The type of composites materials under this investigation are bio-polymers (polylactic acid: PLA) and bio-ceramic (Hydroxyapatite: HA). In this research, the term "The design of the experiment (DOE)" was implemented to find the relation between forming factors including the ratio of HA ratio, molding temperature, and molding pressure. The result showed that the optimum conditions of the bending test were at 5%wt. of HA, 160 °C, 7 MPa of molding temperature and pressure respectively. Biodegradation rate of a specimen was 0.0175 g/day and the specimens acquired a good biocompatibility and they were non-toxic to living cells.